Circulating Adiponectin Is Associated with Renal Function Independent of Age and Serum Lipids in West Africans. (22nd August 2012) - Doumatey, A. P.; Zhou, J.; Huang, H.; Adeleye, J.; Balogun, W.; Fasanmade, O.; Johnson, T.; Oli, J.; Okafor, G.; Amoah, A.; Eghan, B.; Agyenim-Boateng, K.; et al.
Abstract : Adiponectin, a protein secreted by adipose tissue, has been associated with renal dysfunction. However, these observations have not been adequately investigated in large epidemiological studies of healthy individuals in general and in African populations in particular. Hence, we designed this study to evaluate the relationship between adiponectin and renal function in a large group of nondiabetic West Africans. Total adiponectin was measured in 792 participants. MDRD and Cockroft-Gault (CG-) estimated GFR were used as indices of renal function. Linear and logistic regression models were used to determine the relationship between adiponectin and renal function. Adiponectin showed an inverse relationship with eGFR in univariate (Beta MDRD = - 0.18, Beta CG = - 0.26 ) and multivariate (Beta MDRD = - 0.10, Beta CG = - 0.09 ) regression analyses. The multivariate models that included age, sex, BMI, hypertension, smoking, HDL-C, LDL-C, triglycerides, and adiponectin explained 30% and 55.6% of the variance in GFR estimated by MDRD and CG methods, respectively. Adiponectin was also a strong predictor of moderate chronic kidney disease (defined as eGFR < 60 mL/min/1.73 m 2 ). We demonstrate that adiponectin is associated with renal function in nondiabetic West Africans. The observed relationship is independent of age and serum lipids. Our findings suggest that adiponectin may have clinical utility as a biomarker of renal function.